Movement asymmetry in working polo horses. (21st August 2015) - Pfau, T.; Parkes, R. S.; Burden, E. R.; Bell, N.; Fairhurst, H.; Witte, T. H.
Summary: Reasons for performing study: The high, repetitive demands imposed on polo horses in training and competition may predispose them to musculoskeletal injuries and lameness. Objectives: To quantify movement symmetry and lameness in a population of polo horses, and to investigate the existence of a relationship with age. Study design: Convenience sampled cross‐sectional study. Methods: Sixty polo horses were equipped with inertial measurement units (IMUs) attached to the poll, and between the tubera sacrale . Six movement symmetry measures were calculated for vertical head and pelvic displacement during in‐hand trot and compared with values for perfect symmetry, compared between left and right limb lame horses, and compared with published thresholds for lameness. Regression lines were calculated as a function of age of horse. Results: Based on 2 different sets of published asymmetry thresholds 52–53% of the horses were quantified with head movement asymmetry and 27–50% with pelvic movement asymmetry resulting in 60–67% of horses being classified with movement asymmetry outside published guideline values for either the forelimbs, hindlimbs or both. Neither forelimb nor hindlimb asymmetries were preferentially left or right sided, with directional asymmetry values across all horses not different from perfect symmetry and absolute values not different between left and right lame horses (P values >0.6 for all forelimb symmetry measures and >0.2 for all hindlimb symmetry measures). None of the symmetry parameters increased or decreased significantly with age. Conclusions: A large proportion of polo horses show gait asymmetries consistent with previously defined thresholds for lameness. These do not appear to be lateralised or associated with age.